The Ordinariness of Code-meshing in the Indonesian Linguistic Landscapes - Setiono Sugiharto (Journal of Language and Literature, 2022)
Code-meshing as a strategic linguistic practice has been considered a rarity in a high-stake writing practice (e.g. academic writing). Studies in composition scholarship have demonstrated that such a practice needs arduous intellectual endeavors and extra rhetorical efforts to be realized. That is, code-meshing requires an exceptionally high linguistic adeptness, language awareness, and rhetorical sensitivity in order to be performed effectively. As such, the products of code-meshing in scholarly writing are often seen as a marked form of textual realization. This article shows that while strenuous struggles are needed to practice code-meshing in academic writing (i.e. high-stake translingual practice), such a practice can be performed as mundane, ordinary, unremarkable, and relaxed activities (i.e. low-stake translingual practice) in linguistic landscapes or signage displayed in public places. Illustrations of the code-meshed texts in the latter case will be provided, and then examined to account for their ordinariness.  In light of the vibrant low-stake translingual practice, I shall develop an important notion of grassroots performativity to suggest the everydayness of quotidian language practices enacted by multilingual language users in their own community.